2000
DOI: 10.1152/ajpgi.2000.279.4.g757
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus alters paracellular permeability and energy metabolism in Caco-2 cells

Abstract: Rotaviruses infect epithelial cells of the small intestine, but the pathophysiology of the resulting severe diarrhea is incompletely understood. Histological damage to intestinal epithelium is not a consistent feature, and in vitro studies showed that intestinal cells did not undergo rapid death and lysis during viral replication. We show that rotavirus infection of Caco-2 cells caused disruption of tight junctions and loss of transepithelial resistance (TER) in the absence of cell death. TER declined from 300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
113
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(124 citation statements)
references
References 52 publications
(63 reference statements)
6
113
1
4
Order By: Relevance
“…Most of rotavirus permeability studies have been performed in vitro, on cell monolayers, which showed a disruption of tight junctions, decrease of transepithelial resistance 95,96 and increased transepithelial permeability to macromolecules 96 . The effect of paracellular leakage might be induced by NSP4 97 .…”
Section: Paracellular Permeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Most of rotavirus permeability studies have been performed in vitro, on cell monolayers, which showed a disruption of tight junctions, decrease of transepithelial resistance 95,96 and increased transepithelial permeability to macromolecules 96 . The effect of paracellular leakage might be induced by NSP4 97 .…”
Section: Paracellular Permeabilitymentioning
confidence: 99%
“…Moreover, Johansen et al 165 found that children with acute rotavirus infection excreted significantly less PEG of all sizes than control children and children with enteropathogenic Escherichia coli infections. Permeability studies performed in vitro, on cell monolayers, have however showed a disruption of tight junctions, decrease of transepithelial resistance 95,96 and increased transepithelial permeability to macromolecules 96 . The significant discrepancies between in vivo and in vitro studies is most likely due to the absence of hormone regulation, nerves and authentic non--transformed cells in the in vitro systems.…”
Section: Paper II Rotavirus Infection Increases Intestinal Motility Bmentioning
confidence: 99%
“…However, a series of observations suggest that pathogens can directly regulate metabolic responses. Rotavirus infection of an intestinal cell line (Caco-2) leads to metabolic dysfunction characterized by increased production of lactate, decreased mitochondrial function, and reduced intracellular ATP content (18). Viral mitochondria-localized inhibitor of apoptosis, a mitochondria-localizing protein encoded by the human CMV genome, also has been shown to inhibit ATP synthesis in infected cells, causing lower steady state ATP levels (19).…”
mentioning
confidence: 99%
“…Infection by rotavirus of Caco-2 cells causes concurrent drops in transepithelial resistance and epithelial ATP concentrations (Dickman et al, 2000). In rumen epithelia, low mucosal pH and local ATP depletion are directly linked to increased epithelial permeability (Aschenbach et al, 2000).…”
Section: Metabolic Stress and Barrier Integritymentioning
confidence: 99%